(untitled) (Journal of Pharmaceutical Negative Results, 2022)
The aim of this study is to assess the number of RCT done in the maxillary anteriors among patients with Class III caries . The study includes patients visiting the OP of Saveetha Dental College diagnosed with class III caries on the maxillary anteriors and to find the number of RCTs done among those patients. The results were statistically analysed using SPSS software. Descriptive statistics and chi-square tests were done for gender and diagnosis of the tooth. Among a total of 345 patients diagnosed with class III caries on the maxillary anteriors, 21.74% have undergone RCT while 78.26% of the patients did not undergo RCT. The incidence of RCT done in patients with Class III caries was found to be low. This might be due to the aesthetic consideration of the patients and hence early treatment.